Closing the gap: a roadmap to single-cell regulatory genomics - Carnesecchi, Julie; Lohmann, Ingrid (Molecular systems biology, 2020)
Studying the spatiotemporal control of gene regulatory networks at the single-cell level is still a challenge, yet it is key to understanding the mechanisms driving cellular identity. In their recent study, Aerts and colleagues (Gonzalez-Blas et al, 2020) develop a new strategy to spatially map and integrate single-cell transcriptome and epigenome profiles in the Drosophila eye-antennal disc and to deduce in each cell precise enhancer-to-gene activity relationships. This opens a new era in the transcriptional regulation field, as it allows extracting from each of the thousands of cells forming a tissue the critical features driving their identity, from enhancer sequences to transcription factors to gene regulatory networks.
Gesehen am 02.07.2020